On the nature of radar backscatter and 250 MHz scintillation linked with an intense daytime Es patch - Patra, A.K.; Chaitanya, P. Pavan; Bhattacharyya, A. (My University, 2012)
In this paper we present and analyze the Gadanki radar observations of an unusual event of daytime radar echoes from the E region, which spread over a range of 105–150 km and displayed a “U shape” in the range-time SNR map. The U shape echoing structure was an added feature to the commonly observed lower E region echoes with slowly descending features and 150 km echoes with range migration displaying a forenoon descent and afternoon ascent. Distinctly different Doppler velocities were observed in the two arms of the U shape structure with velocities increasing with height and surprisingly exceeding the Doppler velocities of the 150 km echoes. The Doppler spectra display features very similar to those observed below 100 km indicating turbulence as the underlying process. A collocated ionosonde observed unusually strong sporadic E (Es) activity with maximum reflected/scattered frequency (ftEs) reaching 16 MHz in close correspondence with the U shape structure. During the same duration, a collocated 250.6 MHz scintillation receiver revealed scintillation activity, not observed before from Gadanki. The unusual radar observations, strong Es activity, and daytime scintillation are first of its kind from Gadanki. Detailed analysis suggests that the U shape radar echoes extending to 150 km range were due to the sidelobe detection of the E region irregularities with special features that were also responsible for the daytime scintillation. The genesis and implication of the irregularities are discussed.
Keywords: Plasma irregularities; Scintillation; Radar